Fireboat the heroic adventures of the John J. Harvey - Kalman, Maira 1949- (G.P. Putnam's Sons, 2002)
A fireboat, launched in 1931, is retired after many years of fighting fires along the Hudson River, but is saved from being scrapped and then called into service again on September 11, 2001